Investigation of effects of computer anxiety and internet attitudes on computer self-efficacy - Tuncer, Murat (My University, 2012)
During the use of computers in education or in computer based programs one must have information regarding the state of learners’ affective behaviors. Learners’ attitudes and perceptions towards new technologies are quite effective on their learning levels. In this research, effects of computer anxiety and internet attitude on computer self-efficacy were investigated. According to the research findings, computer anxiety has a strong influence on internet attitudes. Moreover, it was concluded that internet attitude affected computer self-efficacy. On the other hand, a significant relation between computer anxiety and computer self-efficacy could not be determined. Based on these findings, we may suggest that by keeping computer anxiety under control, we may be able to positively develop learners’ internet attitudes. We may further suggest that students who have positive internet attitude also have relatively enhanced computer self-efficacy.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Computer anxiety; Computer self-efficacy; Internet attitudes; Computer education; Instructional technology